2009
DOI: 10.1016/s0924-9338(09)70888-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Psychosocial Stress and Depression among Adolescents

Abstract: Background:The data of various studies indicates, that stressful life events having a strong influence to the development of depression in adolescence.Aim:To study the correlation between psychosocial stress and depression among adolescents.Methods:The subjects of the study were 1026 schoolchildren (519 boys and 507 girls) of secondary schools (ninth form pupils) of one administrative region of Lithuania. Average age of adolescents was 14,8±1,12 years. The 57-item Depression scale of Minnesota Multiphasic Pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Psychosocial stress was assessed by The Reeder Stress Inventory (RSI), measuring subjectively perceived stress, was used to determine psychosocial stress [ 48 ]. In the quasi-experimental trial, we used an adapted seven-item RSI (LT-RSI) that was validated for use in the Lithuanian language [ 49 ]. The scale includes statements with responses based on a 4-point Likert scale from 1 ( No, I disagree ) to 4 ( Yes, I agree ).…”
Section: Methodsmentioning
confidence: 99%
“…Psychosocial stress was assessed by The Reeder Stress Inventory (RSI), measuring subjectively perceived stress, was used to determine psychosocial stress [ 48 ]. In the quasi-experimental trial, we used an adapted seven-item RSI (LT-RSI) that was validated for use in the Lithuanian language [ 49 ]. The scale includes statements with responses based on a 4-point Likert scale from 1 ( No, I disagree ) to 4 ( Yes, I agree ).…”
Section: Methodsmentioning
confidence: 99%
“…Body image is a schematic own body representation, comprised on the basis of space, time and movement experience (Sporto terminų žodynas, 2002). A lot of attention is paid to a negative body image component, which is body dissatisfaction, looking for ties to depression (Kardelis, Stakytė, 2003;Markevičiūtė et al, 2003;Didžiokienė, Žemaitienė, 2005) and eating disorders (Barker, 2003;Vizbaraitė et al, 2007;Jankauskienė, 2008;Pelegrini, Petroski, 2010). Conducted studies revealed that the majority of adolescents (especially girls) believed that appearance and other people's opinion formed basis for self perception (Blond, 2008).…”
mentioning
confidence: 99%